(untitled) (Innovative Technologica: Methodical Research Journal, 2021)
The article considers the question of the optimal impact speed during the destruction of soil lumps from an energy point of view, proposes a new methodology for assessing based on newly formed surfaces after the destruction of soil lumps, derives a dependence for determining the specific energy spent on crushing soil lumps, presents the experimental procedure and experimental results on Based on the data obtained, conclusions are drawn.